How Different is the Efficiency of Public and Private Water Companies in Asia? - Estache, Antonio; Rossi, Martin A. (Washington, DC: World Bank, 2014)
Several studies have compared the efficiency of publicly and privately owned water utilities and reached conflicting conclusions on the impact of ownership on efficiency. This article provides further evidence by estimating a stochastic cost frontier for a sample of Asian and Pacific regional water companies. The results show that efficiency is not significantly different in private companies than in public ones.